A Systematic Review of TaRL-Based and Digital Student Worksheets for Enhancing Learning Outcomes - Jesinta Amabell Jonathan; Siti Rohmah Nurhayati (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
Despite the widespread use of Student Worksheets (LKPD) in Indonesian classrooms, limited attention has been given to synthesizing how innovative LKPD designs, particularly those integrating differentiated instruction and digital technology, contribute to student learning outcomes. This study aims to systematically review the effectiveness of TaRL-based and digital LKPD (e-LKPD) designs in enhancing learning outcomes across educational contexts. Employing the PRISMA framework, a systematic search was conducted in Google Scholar, Scopus, and JSTOR for studies published between 2013 and 2023. Of 30 studies meeting the inclusion criteria, data were synthesized using qualitative thematic analysis. The findings reveal that TaRL-based LKPD facilitates differentiated learning by aligning materials with students' ability levels, while e-LKPD enhances flexibility, accessibility, and student engagement through interactive digital features. Both approaches were associated with improved conceptual understanding, critical thinking, and active participation. However, substantial variation in research designs and outcome measures limits the generalizability of findings. This review contributes to the educational literature by providing a comprehensive synthesis of LKPD innovations, identifying design features that effectively support 21st-century learning, and highlighting the need for cross-disciplinary research and more robust empirical designs. The implications suggest that educators and curriculum developers should prioritize adaptive, technology-integrated LKPD designs, while future research should employ longitudinal and comparative methods to establish causality.